The microstructure characterization and elastic properties of closed-cell foams. (5th December 2022) - Su, Bo-Yuan; Jang, Wen-Yea
Abstract: The present study investigated the microstructure and compressive response of ALPORAS closed-cell foam. The micro-CT technique was adopted to study the interior structure of the foam. Image processing algorithms were then incorporated to measure the geometrical characteristics of the foam cellular microstructure, including the size, surface area, geometrical shape, aspect ratio, and sphericity of cells. The cells were irregular polyhedra with approximately 14–15 faces and 5 edges per face; they had longer dimensions in the gravitational direction than in the other two mutually orthogonal directions. Three statistical measurements were employed in the development of random 3D numerical models based on the Laguerre tessellation of random close packed spheres along with three probability density functions for sphere size distributions. The effects of parameters such as probability density functions, sphere volume fraction, and coefficient of variation in sphere volume on the geometrical characteristics of the developed numerical models were examined. The difference in geometric characteristics of the numerical models generated using different probability functions was nonsignificant. Numerical simulations were subsequently conducted using the developed numerical models. The comparison between numerical and experimental results revealed that numerical models overestimated the experimental value by a factor of approximately 3. This discrepancy can be attributed to the difference in detailed microstructural features between the generated numerical models and real foam.